2018
DOI: 10.24036/020187210736-0-00
|View full text |Cite
|
Sign up to set email alerts
|

Supervision in counseling service based on psychological test result to student’s learning satisfaction

Abstract: As a profession, guidance and counseling have a supervision procedure in order to maintain and evaluate purpose to make evaluatif decision in guidance and counseling service. A supervision it self not only about process and result of counseling service, but also an asessment using psychological test, this asessment was useful for complete an inforrmation about psychological competence and individual difference of student. This result of psychological tes will benefit for counselor and also for student to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Similar studies have demonstrated that the participants' unique traits and psychological factors nuance the relationship between a teacher's emotional support and a student's level of school engagement (Wang & Ecless, 2013;Prasetyo et al, 2018). Students' academic self-concepts are positively correlated with the extent to which they get emotional support during learning activities (Ramadhan, 2019;Yuzarion et al, 2018;Aristya & Rahayu, 2018;Kim et al, 2018). Academic self-concept is a moderator variable that boosts both teachers' encouragement and students' interest in learning.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Similar studies have demonstrated that the participants' unique traits and psychological factors nuance the relationship between a teacher's emotional support and a student's level of school engagement (Wang & Ecless, 2013;Prasetyo et al, 2018). Students' academic self-concepts are positively correlated with the extent to which they get emotional support during learning activities (Ramadhan, 2019;Yuzarion et al, 2018;Aristya & Rahayu, 2018;Kim et al, 2018). Academic self-concept is a moderator variable that boosts both teachers' encouragement and students' interest in learning.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…To address these challenges, it is imperative to provide comprehensive training programs that equip counselors with the necessary skills and knowledge to navigate and engage with diverse cultural contexts. Encouraging counselors to actively interact with individuals from different backgrounds and facilitating opportunities for comparative social studies can further enhance their multicultural competence (Ponterotto, 2008;Yuzarion et al, 2018).…”
Section: The Foundation Dimension Of Counselorsmentioning
confidence: 99%
“…According to Farid Poniman, a person's genetic potential is usually difficult to change, because it comes from their DNA [20]. Therefore, it is important for parents and teachers to determine the genetic potential of children to properly direct them in choosing a career, and implementation of psychological counseling [21]. This research is, therefore, focussed on introducing studies and STIFIn test utilization in Senior High Schools (SMA) to enable students plan a better future in accordance with the 4.0 industrial revolution era.…”
Section: Introductionmentioning
confidence: 99%